THE HISTORY OF VOLEYBALL DEVELOPMENT IN UKRAINE - Anna Galytska (Lesya Ukrainka Volyn National University, 2017)
The relevance of the investigation is determined by the need of studying the regularities of volleyball development in Ukraine. Methods of research: analysis and synthesis of scientific literature and archival data, analysis and synthesis, induction and deduction, historical and logical methods. Results of the work. Volleyball was organized in Kharkiv in 1925. Only three years after the introduction of the game, Ukrainian volleyball players reached the highest levels of the pedestal of the All-Union Spartakiad in 1928. Volodymyr Blyakh played a leading role in the rapid development of volleyball. He is a doctor of medical sciences, a professor. The real triumph was the performance of the national teams of Ukraine in 1956 at the 1st Spartakiad of the USSR: gold medals were won by men. The development of volleyball allowed residents of Kharkiv Yuri Vengerovsky, and Yuriy Poyarkov, a resident of Odesa Eduard Sybiryakov as part of the Soviet team to win gold medals at the Olympic Games in 1964. Four years later, seven Ukrainian volleyball players (Vasylius Matushevas, Yuriy Poyarkov, Volodymyr Belyaev, Yevhen Lapynsky, Victor Mykhalchuk, Volodymyr Ivanov, Borys Tereshchuk) reached the highest step of the pedestal. In total, Ukraine has 14 Olympic champions, 11 world champions, 27 winners of European forums. Conclusions. Volleyball began its expansion in Ukraine in the early twentieth century. Sport teams, sport clubs, and competitions were organized. A large number of Ukrainian athletes have become famous all over the world, being part of teams at the Olympic Games, world championships and European championships.